Epidemiological perspectives of amyloidosis in Argentina: a cohort study analysing incidence and mortality patterns among a population affiliated to a medical care programme - María Lourdes Posadas-Martínez; Delfina Cirelli; Florencia De Florio; María Adela Aguirre; Elsa Mercedes Nucifora; Patricia Beatriz Sorroche; María Soledad Sáez; Valeria Inés Aliperti; Jimena Vicens; Marcelina Carretero (BMJ Public Health)
Background Data on the epidemiology of amyloidosis are scarce worldwide, making it difficult to understand its true incidence and mortality.Aim The aim of this study is to estimate the incidence and mortality rate of systemic amyloidosis in people affiliated to a Medical Care Program in the city of Buenos Aires, Argentina.Methods This is a hospital-based prospective study. All affiliates over 17 years to the Medical Care Program of the Hospital Italiano de Buenos Aires, and incident cases and deaths due to amyloidosis from the Institucional Amyloidosis Registry from 1 January 2011 to 31 December 2022 were included. Incidence and mortality rates were reported per million person-year with their respective 95% CIs. Crude, standardised and stratified rates were determined.Results During the study period, the crude incidence rate was 63 (95% CI 52 to 76) and the crude mortality rate was 31 (95% CI 23 to 40) cases per million person-year, with the wild-type transthyretin amyloidosis (ATTRwt) subtype having the highest rates. Men were more affected, especially from the age of 70 years onwards. In addition, an increase in the incidence and mortality rate was observed throughout the period studied.Conclusion The results of this study indicate that amyloidosis remains a rare disease but with an increase in incidence in recent years, especially in elderly people. This underlines the importance of further research in epidemiology for a better understanding of the pathology and its evolution.